Comparision of success rate of arterio-venous fistula in patients with diabetes vs non-diabetes (Journal of Society of Surgeons of Nepal, 2016)
Introduction: Definition of chronic renal disease is based on the presence of kidney damage or glomerular filtration rate (GFR 60 ml/min per 1.73 m2) for 3 months, irrespective of cause. Once they are diagnosed as CKD, they are kept either on hemodialysis or peritoneal dialysis or patient undergo renal transplant. With this research we may prove that even in a similar circumstances failure rate of AVF is more in diabetes patient.Methods: Total 50 patients of either gender were taken in this study. Inclusion criteria: CRF with GFR 1.5mm and venous diameter >2mm. Preoperative radial artery blood flow >30cm/min. Exclusion criteria: arterial diameter